Impact of Ecology on the Productivity of Road Commercial Vehicles - Smerdu, Ivan (Promet - Traffic&Transportation, 2012)
It is understandable that any measure affecting the productivityof road commercial vehicles is faced with opposition bythe holders and operators oftransp011 companies. This oppositionis so much the greater as much as its preparation and presentationhave been insufficient. The opinion that ecologicalmeasures have a negative impact on the productivity of roadcommercial vehicles is quite widespread: however, laying sucha great stress on that opinion is rather exaggerated. In the courseof introducing ecological measures, a fall in productivity occurs,as a rule, which applies to the time required for the transportcompanies to adapt to it. The duration of the adaptationstage depends on the type of measure and the viability of thecompanies. If the adaptation of entetprises is integral and efficient,the original productivity will be swpassed after the initialfall.